PENGARUH PROFITABILITAS, PAJAK PERUSAHAAN, LIKUIDITAS, TERHADAP LEVERAGE - Mokhammad Gati Jayeng Wibowo (Jurnal Akuntansi dan Pajak, 2023)
In order to realize management’s goal in supervising the company is to gain maximum profit and be able to control current and future conditions. The manager is fully responsible for the balance between assets and liabilities, as well as determining best composition between the two. The selection of this assets and liabilities structure will then determine the wealth. The determination of management decisions on financial management is then related to the origin of the funds to be used, balanced financing targets, and optimal capital structure. Funds fulfillment considers how the company obtains it, from its own sources such as retained earnings or from outside sources such as debt, issues of shares and/or bonds. Recently, non-financial companies makes users to compete fiercely in terms of efficiency in all things if their companies want to remain globally competitive. Every non-financial company has to apply economic principles, generally not only pursue how much profit they will take, but also able to capture all significant and measurable potentials on the variables of profitability, growth opportunity, tangibility, liquidity, tax-shield, earning volatility and cash-flow volatility. The benefits of this study is to provide consideration for management in making financial decisions, especially in determining the optimum capital structure for non-financial companies. Keywords: leverage, profitability, tax, liquidity, non-financial company